2019
DOI: 10.1108/ijbm-08-2018-0229
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the impact of financial incentives on NFC mobile payment adoption

Abstract: Purpose The purpose of this paper is to investigate the effects of financial incentives on consumers’ intention to adopt near field communication (NFC) mobile payment. Design/methodology/approach An online experiment was conducted crossing two levels of incentive types (cash back and discount), two levels of incentive amounts (5 and 10 percent), and two levels of incentive promotion periods (one and three months). A total of eight treatment conditions plus one control group comprised the 2×2×2 factorial desi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
42
0
5

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 74 publications
(62 citation statements)
references
References 44 publications
3
42
0
5
Order By: Relevance
“…In the m-payment context, researchers (e.g., Alaeddin et al, 2018;Kalinic et al, 2019a;Liébana-Cabanillas et al, 2014bMatemba & Li, 2018;Ramos de Luna et al, 2016;Su et al, 2018;Zhao et al, 2019) have used TAM. UTAUT/UTAUT2 were used by other researchers (e.g., Gupta & Arora, 2019;Madan & Yadav, 2016;Oliveira et al, 2016;Shaw, 2015;Wang & Yi, 2012;Widodo et al, 2019).…”
Section: Mobile Payment Adoption Researchmentioning
confidence: 99%
See 2 more Smart Citations
“…In the m-payment context, researchers (e.g., Alaeddin et al, 2018;Kalinic et al, 2019a;Liébana-Cabanillas et al, 2014bMatemba & Li, 2018;Ramos de Luna et al, 2016;Su et al, 2018;Zhao et al, 2019) have used TAM. UTAUT/UTAUT2 were used by other researchers (e.g., Gupta & Arora, 2019;Madan & Yadav, 2016;Oliveira et al, 2016;Shaw, 2015;Wang & Yi, 2012;Widodo et al, 2019).…”
Section: Mobile Payment Adoption Researchmentioning
confidence: 99%
“…However, perceived trust, social value, and convenience were insignificant in influencing users' satisfaction. Zhao et al (2019) extended TAM with financial incentives and perceived risk to investigate the factors which identified consumers' intention to adopt NFC m-payments. Their study found that the availability of financial incentives did not have a direct effect on intention to adopt NFC m-payment; however, financial incentives indirectly affected consumers' intention through perceived risk.…”
Section: Mobile Payment Adoption Researchmentioning
confidence: 99%
See 1 more Smart Citation
“…Penelitian oleh Ma et al (2018) menemukan bahwa resiko keuangan memiliki efek negatif pada niat pengguna untuk menggunakan mobile payment, dikarenakan ketika pengguna merasakan adanya resiko kerugian finansial pada penggunaan mobile payment, niat pengguna untuk menggunakan mobile payment tersebut akan melemah. Ini mendukung hasil beberapa studi termasuk penelitian oleh Zhao et al (2019).…”
Section: IIunclassified
“…Hasil pengujian ini didukung oleh beberapa penelitian yang telah dilakukan oleh Pauchard (2019), Reith et al (2019), Zhao et al (2019) dan Ma et al (2018) yang menemukan bahwa adanya pengaruh signifikan negatif dari persepsi resiko keuangan terhadap niat penggunaan mobile payment. Bisa diambil kesimpulan bahwa persepsi resiko keuangan merupakan faktor penentu yang berpengaruh terhadap intensi penggunaan mobile payment.…”
Section: Vunclassified